2006
DOI: 10.1016/s0022-5347(05)00051-0
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Blood Loss Predicts the Development of Urinary Extravasation on Cystogram Following Radical Retropubic Prostatectomy

Abstract: The extent of postoperative bleeding predicts the extent of urinary extravasation on initial cystography. It may be a useful measurement for identifying men who can safely undergo early catheter removal without cystography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Predictors of anastomotic extravasation have been difficult to identify. Investigators failed to show that pelvic drain output volume, pelvic drain fluid creatinine level, body mass index, surgical specimen weight, number of anastomotic sutures, or the presence of intraoperative extravasation were significant predictors of postoperative anastomotic extravasation, thereby prompting recommendations for taking a cystogram in all candidates deemed suitable for early catheter removal [1,8,9]. Chodak et al.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of anastomotic extravasation have been difficult to identify. Investigators failed to show that pelvic drain output volume, pelvic drain fluid creatinine level, body mass index, surgical specimen weight, number of anastomotic sutures, or the presence of intraoperative extravasation were significant predictors of postoperative anastomotic extravasation, thereby prompting recommendations for taking a cystogram in all candidates deemed suitable for early catheter removal [1,8,9]. Chodak et al.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors investigated factors such as postoperative haemoglobin or haematocrit level or intraoperative and postoperative bleeding as predictors for an anastomotic extravasation. A direct correlation between postoperative haemoglobin loss and the size of a urinary extravasation was found by Fening et al [25] in a series of 826 patients investigated after RRP. They hypothesized that a haematoma caused by postoperative bleeding (decrease of more than 6.2 haematocrit points) causes distraction of the anastomotic region and is thereby responsible for extravasation [25].…”
Section: Discussionmentioning
confidence: 61%
“…A direct correlation between postoperative haemoglobin loss and the size of a urinary extravasation was found by Fening et al [25] in a series of 826 patients investigated after RRP. They hypothesized that a haematoma caused by postoperative bleeding (decrease of more than 6.2 haematocrit points) causes distraction of the anastomotic region and is thereby responsible for extravasation [25]. There seems to be a relation between extravasation and blood loss, but the mechanism is still not properly understood.…”
Section: Discussionmentioning
confidence: 61%
“…Factors predisposing to extravasation at the vesicourethral anastomosis within the first week following RRP are poorly understood. According to recent studies, either watertight anastomosis or extent of bladder-neck reconstruction were unrelated to urinary leakage [10,11]. Fenig et al [11] demonstrated that even moderate or marked leakage was not associated with increased risk of AS or incontinence provided that the catheter was left indwelling until the resolution of urinary drainage.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, either watertight anastomosis or extent of bladder-neck reconstruction were unrelated to urinary leakage [10,11]. Fenig et al [11] demonstrated that even moderate or marked leakage was not associated with increased risk of AS or incontinence provided that the catheter was left indwelling until the resolution of urinary drainage. The magnification of laparoscopic technology provides surgeons with a more precise anatomic dissection of the prostate from surrounding tissue and watertight anastomotic suturing.…”
Section: Discussionmentioning
confidence: 99%